Association between Pan‐Immune Inflammation Value and Sarcopenia in Hypertensive Patients, NHANES 1999–2018 - Lu Long; Bingquan Xiong; Zhidan Luo; Haiyan Yang; Qiang She (The Journal of Clinical Hypertension)
ABSTRACT Sarcopenia worsens the prognosis in hypertensive patients, leading to complications such as proteinuria, osteoporosis, disability, and cognitive impairment. Early screening and intervention for sarcopenia in these patients may improve outcomes. This cross‐sectional study utilized data from 9253 hypertensive patients in the 1999–2018 National Health and Nutrition Examination Survey (NHANES). We used logistic and linear regression models, restricted cubic splines (RCS), and subgroup analyses to evaluate the relationship between pan‐immune‐inflammation value (PIV) and sarcopenia. Patients were divided into quartiles based on PIV levels. After controlling for confounding factors, our study found that those in the highest PIV quartile faced a 36% greater risk of developing sarcopenia compared to those in the lowest quartile (OR = 1.36, 95% confidence interval [CI]: 1.04–1.77). The RCS analysis indicated a linear increase in sarcopenia risk as PIV levels rose (non‐linear p = 0.130). Subgroup analysis demonstrated that diabetes synergistically increased sarcopenia risk (p for interaction = 0.007). Elevated PIV levels were identified as an independent risk factor for sarcopenia, with diabetes amplifying this risk. These findings highlight the importance of early identification and management of elevated PIV levels to improve outcomes for hypertensive patients at risk of sarcopenia.